The prevalence of alcohol use disorders among university students in developing countries: a systematic review and meta-analysis - Ndlovu, Philani (Rhodes University, Faculty of Humanities, Department of Psychology)
High alcohol misuse is associated with many challenges, including (a) unsafe sex, problems with the criminal justice system, absenteeism, academic failure, death, injury, and alcohol related harm, both in the developing and developed world. Despite the above, no meta-analysis had been conducted in the literature to comprehensively study the prevalence of Alcohol Use Disorders (AUDs) amongst university students in the developing world. This study reviewed literature related to AUDs among university students in developing countries. It described the concept of AUD and the harmful effects of excessive alcohol use, including biological, cognitive, psycho-social, and economic impacts on the individual and the family.
Keywords: College students -- Alcohol use -- Developing countries; College students -- Conduct of life; College students -- Attitudes; Alcohol -- Physiological effect